Enhancing Internet Interference Complaint Resolution: A Case of Object-Oriented Systems Approach at Kominfo Kota Gorontalo - Ita Permatahati; Rahmat Taufik R.L Bau; Hermila A; Siti Sabrina Ramadanti Abdul (Jurnal Riset Sistem dan Teknologi Informasi, 2023)
In order to address and manage complaints arising from disruptions to internet networks or services, especially among various agencies, the Gorontalo City Information and Encryption Communication Service has implemented an information system. This system facilitates the reception, processing, and resolution of complaints from these agencies within the city. Notably, observations reveal potential areas for enhancement within this system, including the lack of comprehensive complaint details upon successful submission by the complainant (client) and the absence of a ticketing system. This study is focused on examining the role of the Object-Oriented System Approach in resolving issues within Kominfo Kota Gorontalo. Employing a descriptive qualitative methodology, the research employed data collection methods such as observation, interviews, and literature review. The findings underscore the efficacy of the Object-Oriented Analysis & Design (OOAD) in effectively addressing the identified challenges within the Gorontalo Office of Communication, Informatics, Statistics, and Encryption.